Ultra-Stable and Highly Efficient White Light Emitting Diodes through CsPbBr3 Perovskite Nanocrystals-Silica Composite Phosphor Functionalized with Surface Phenyl Molecules - Yoon Soyeon; Seo min jun; Kim, In Soo; Lee, Kwangyeol; Woo, Kyoungja (Wiley - V C H Verlag GmbbH & Co., 2023)
Poor stability of CsPbBr3 perovskite nanocrystals (NCs) to moisture/heat/light has significantly limited their application as a green phosphor, despite their outstanding luminescent properties. Here, a remarkably stable CsPbBr3 NCs-silica composite phosphor functionalized with surface phenyl molecules (CsPbBr3-SiO2Ph) is synthesized by controlling low-temperature hydrolysis and condensation reaction of perhydropolysilazane in the presence of CsPbBr3 NCs followed by phenyl-functionalization. Through the process, CsPbBr3 NCs are confined in a compact silica matrix, which is impermeable to H2O. The synthesis strategy is extended to a classical red quantum dot, CdZnSeS@ZnS NCs, to fabricate a white light emitting diode (WLED) consisting of CsPbBr3-SiO2Ph and CdZnSeS@ZnS-SiO2Ph phosphor and silicone resin packaged on a commercial blue InGaN chip with luminous efficacy (LE) of 9.36 lm W-1. The WLED undergoes enhancements in both green and red photoluminescence over time to achieve a highly efficient performance of 38.80 lm W-1. More importantly, the WLED exhibits unprecedented operational stability of LE/LE0 = 94% after 101 h-operation at 20 mA (2.56 V). The ultra-high operational stability and efficient performance are mainly attributed to thermal curing and aging through which grain growth occurs as well as deactivation of defect states by permeated atmospheric O-2.